DIJK, Teun A. van. Discurso e poder/ Hoffnagel, J. & Falcone, K. (Orgs.) São Paulo: Contexto, 281 págs. (Cadernos de Linguagem e Sociedade, 2010)
DIJK, Teun A. van. Discurso e poder/ Hoffnagel, J. & Falcone, K. (Orgs.) São Paulo: Contexto, 281 págs.